Genetic variations for herbicide tolerance (Imazethapyr) in chickpea (Cicer arietinum) - CHATURVEDI, S K; MURALEEDHAR, ASKI; GAUR, P M; NEELU, MISHRA; SINGH, KULDEEP; NADARAJAN, N (The Indian Journal of Agricultural Sciences, 2014)
Plant resistance has been widely recognized as the most potential and successful way to minimize losses due to biotic stresses including weeds in chickpea (Cicer arietinum L.). Weeds pose great threat to chickpea production through competing for natural resources. Herbicides are the most successful weed controlling agents. Presently we do not have chickpea genotypes having tolerance to post emergence herbicides. This study was undertaken to identify the sources of resistance to the post emergence herbicide in chickpea. 509 chickpea accessions (reference set and elite breeding lines) were screened during September to November 2011 for the post emergence herbicide Imazethapyr (Pursuit™) tolerance. After preliminary screening, 31 most tolerant and 9 most sensitive genotypes were identified. Later these 40 genotypes were re-evaluated during November 2011 to February 2012. Accessions, viz. ICC 1164, IPC 2010-81 and IPC 2008-59 were found to be most tolerant. Lines such as ICC 8522, ICC 6874 and ICC 5434 were recorded as the most sensitive.